Stigmatisation of people experiencing gambling-related harms: a vignette study of the predictors of desire for social distance - Lloyd, Joanne; Penfold, Katy L.; Chadwick, Darren David; Nicklin, Laura Louise; Hinton, Daniel P.; Dinos, Sokratis (Frontiers in Psychology, 2025)
IntroductionStigma is associated with psychological distress and can act as a barrier to help-seeking for people who experience gambling harms. While research into intersectional stigma within this population is scarce, this may be exacerbated for those from multiply-marginalised groups.MethodThis study used an online survey with ‘vignette’ design to capture attitudes of 3,567 adults in Great Britain towards hypothetical individuals experiencing gambling harms alongside a variety of other potentially stigmatised characteristics (minority ethnicity, LGBTQ status; low-income status; chronic drug/alcohol use; and mental health difficulties). Questions about participants’ own demographic characteristics, their contact with and experience of gambling/gambling harms, and their beliefs about the nature and origin of gambling harms were also administered.ResultsSignificantly greater desire for social distance from protagonists experiencing gambling harms than those described as gambling recreationally (p < 0.05) indicated the presence of public stigma, and this was further elevated (p < 0.05) when the protagonist was described as having difficulties with drug and alcohol use. The other potentially stigmatised characteristics were not associated with an additional increase in stigma, and potential reasons for this are discussed. Perceived disruptiveness and harmfulness of the protagonist, along with beliefs that gambling harms are due to bad character and difficult to recover from, were all significant predictors of desire for social distance – as were lower levels of prior contact with gambling harms (all p < 0.05).DiscussionThese findings have utility for stigma reduction interventions, and can also inform those working with people experiencing gambling harms.